The role of weather and climate information services to support in wildfire management in Northwestern Europe - H.A. Lambrechts; C.R. Stoof; M. del Pozo; F. Ludwig; S. Paparrizos (Climate Risk Management, 2024)
As climate change intensifies, temperatures rise and extreme weather events become more frequent, leading to increased droughts and elevated wildfire risks. This trend is especially pronounced in with an emerging wildfire risk under climate change, including Northwestern Europe. This study evaluates the use and needs of climate information services (CIS) for supporting Integrated Fire Management in these regions. Employing a qualitative approach, an online survey was distributed to professional stakeholders in Northwestern Europe, focusing on their awareness and perception of preparedness for wildfires, their use of CIS, and their future needs for fire management.Results indicate that while stakeholders are experiencing wildfires and although there is a high perception of preparedness for current wildfire conditions, their preparedness for future conditions is considerably lower. Most rely on short-term weather forecasts, yet there is a significant gap in the use and perceived need for long-term climate projections. Additionally, engagement with and awareness of the European Forest Fire Information System (EFFIS) are limited. The findings underscore the critical need for more detailed and locally relevant CIS that are salient, credible, and legitimate to foster proactive and adaptive management strategies. Enhancing stakeholder engagement and co-producing tailored CIS can contribute to improving prevention, preparedness, and resilience against the escalating threat of wildfires in Northwestern Europe.